Technologies for the reuse of demolition waste in the production of geopolymer-based building materials: prospects and opportunities - D'Angelo Gigliola (Renewable Energy and Environmental Sustainability)
In a climate change scenario that is increasingly affecting our daily lives, it is essential to rethink the reuse of existing resources and avoid the exploitation of raw materials. If we consider the stock of existing buildings in Italy, we cannot ignore the fact that most of them are in a state of decay or in need of major maintenance; the recovery or demolition of these buildings generates a considerable amount of waste that has a negative impact on the environment, from transport to disposal. A sustainable design approach can achieve interesting results in terms of economic, environmental and social impact. Starting from the final phase of the life cycle of buildings, this paper aims to show the possibilities of recovering traditional building materials such as cement, brick and tuff. The use of innovative production technologies will allow the reintroduction of these materials to the market, with consequent benefits in all aspects of the ‘sustainability triad'. The aim of the work is to identify a practical, easy-to-use process for the production of eco-sustainable materials that, while retaining their intrinsic chemical-mineralogical characteristics, can be easily used in the context of the existing built heritage thanks to the compatibility between these new materials and the pre-existing substrate. The innovative results obtained as part of an international research project show how the use of demolition waste for the composition of geopolymer mixtures allows the reuse of large percentages of construction waste, while guaranteeing the mechanical performance of materials produced with traditional techniques, which have a high level of emissions; the production of geopolymers allows an 80% reduction in emissions compared to the production of Portland cement. The paper is intended to serve as a starting point for further in-depth application of the mixtures produced and to provide reflections and future research directions.